Role of training in customer oriented selling activities and in sales performance : a study on firms operating in automotive industry - Sağlık, Dilek (My University, 2005)
In order to be able to satisfy ever-evolving consumer expectations in terms of higher quality and service, sales training plays a dominant role in the companies which excel in their industries. The design and application of sales training therefore constitutes a key factor in the overall success of the companies. This study demonstrates the impact of sales training on customer relations and communication skills in Turkish Automotive Industry Passenger Car Retail Sales. Literature surveys was based on studies conducted in the USA and in Turkey and was used to design a training program. Sales managers and experienced salespeople in the automotive retail sales have also been interviewed to shape the content of the training program. Effectiveness was then measured via a field survey whereby, questionnaires were given to the automobile retail salespeople. The research is of experimental design, where pre-test and three months after post-test conditions were co-ordinated for the salespeople to work within. In three days of sales training, the researcher trained the salespeople in the basic steps of the sales process in the subjects of Approach, Defining Needs, Presentation and Demonstration, Handling Objections and Closing. For customer relations eleven dimensions were analyzed in pre-test and post-test. Among those, the adaptability of behavior, defining needs ability, the win-win approach, and providing a solution reflected that there was a significant change in behavior of the trained people. Communication skills was analyzed based on six dimensions. Among those, transmitting of messages, listening ability, persistency, and summarizing the conversation significant changes were observed in the behavior of the participants of the training program.

Sürekli gelişim gösteren müşteri beklentilerini yüksek kalite ve hizmet ile karşılayabilmede satış eğitimi firmalarda önemli bir rol oynamaktadır. Bu nedenle, satış eğitiminin biçimlendirilmesi ve uygulanması firmaların genel başarısında temel bir unsurdur. Bu çalışma Türk Otomotiv Sanayinde Perakende Binek Araç Satış' larında satış eğitiminin müşteri ilişkileri ve iletişim becerilerine etkisini ölçmektedir. Türkiye'de ve A.B.D.'de yapılmış çalışmalara dayanarak yazın taraması yapılmış ve eğitim zayn edilmiştir. Eğitim programının içeriğinin biçimlendirilmesinde satış yöneticileri ve deneyimli otomotiv perakende satış elemanlarıyla yapılan yüzyüze görüşmeler de katkıda bulunmuştur. Etkililik daha sonra bir saha çalışması yoluyla ölçülmüş, bunun içinde otomotiv perakende satış elemanlarına anketler dağıtılmıştır. Deneysel serim nitelikli bu çalışmada satış elemanlarına eğitim öncesi ve eğitimi izleyen üç ay sonra anketler dağıtılmıştır. Üç günlük satış eğitiminde, araştırmacı katılımcıları satış sürecinin temel aşamalarını oluşturan Karşılama, ihtiyaç belirleme, sunum, test sürüşü, itirazları karşılama ve kapanış konularında eğitmiştir. Müşteri ilişkilerinde test-öncesi ve test-sonrası on bir farklı unsur analiz edilmiştir. Bunlardan davranış uyarlanabilirliği, ihtiyaç belirleme yeteneği, kazan-kazan yaklaşımı, çözüm üretme unsurlarında eğitim almış satış elemanlarının davranışında belirgin farklılık sağlanmıştır. İletişim becerileri altı unsurda analiz edilmiştir. Bunlardan mesajların aktarılması, dinleme yeteneği, kararlılık ve görüşmeyi özetleme unsurlarında eğitime katılan katılımcıların davranışlarında belirgin farklılık gözlemlenmiştir.
Keywords: Genel yönetim; Müşteri İlişkileri; Pazarlama yönetimi; Satış Eğitimi; Satış yönetimi